Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan pada Syariah Hotel Solo - Wijayati, Ami; , Basworo Dibyo, S.E., M.Si (2016)
This study aimed to analyze the influence of leadership style, organizational culture and motivation on employee performance on Syariah Hotel Solo. This type of research is quantitative, the population of all employees Syariah Hotel Solo and sampling using random cluster sampling technique or a simple random. Research data collection techniques through a questionnaire with a scale linker. Based on the results of multiple regression analysis obtained formulations Y = 4.780 + 0.311 X1 + 0.315 X2 + 0,495 X3 + e. where Y is the variable performance of employees, X1 is a style of leadership, X2 and X3 is the organizational culture is the motivation, the three constants of each variable is positive so that said positive influence on employee performance. The t-test studies show variable leadership styles, organizational culture and motivation have a significant positive influence on employee performance. F test results can be analyzed that the three independent variables significantly influence employee performance, where the calculated F value of 15.349 and 0.000 significance level of <0.05. Last test research is a test of determination with R2 values of 0.673, meaning the independent variables have contributed to the variable performance of employees amounted to 67.30%, the rest is explained by other variables outside the model.